Towards improving soft skills of medical education in the 21st century: A literature review - Rilani Riskiyana; Nurul Qomariyah; Rachmadya Nur Hidayah; Mora Claramita (International Journal of Evaluation and Research in Education (IJERE), 2022)
Global challenge forced medical education to be transformative in preparing the future health care professional. Student-centered learning (SCL) has been regarded as the most suitable medical curriculum approach to meet the health care demand. Indonesia, with its hierarchical and collectivistic culture, has long implemented SCL. The necessary skills are needed to be identified to improve the medical curriculum in Indonesia. We did a literature review to generate soft skills for the health care professionals. We distributed the list to stakeholders and medical teachers for a two-round Delphi study. We identify 26 soft skills through literature review. The Delphi study's first-round yielded 95 responses comparing the expectation and reality of the 26 soft skills in the current medical curriculum. The second round Delphi study was performed towards the similar participants to gather the final set of soft skills recommended for curriculum improvement in medical and health professions education. Soft skills, though considered necessary, are not well-understood yet. The unfamiliarity influenced the irresolute delivery of soft skills in medical schools. Faculty developments are recommended to improve the understanding and capability of teachers to facilitate the learning of soft skills.